GM-CSF Programs Hematopoietic Stem and Progenitor Cells During Candida albicans Vaccination for Protection Against Reinfection - Bono, Cristina; Guerrero, Paula; Jordán-Pla, Antonio; Erades, Ana; Salomonis, Nathan; Grimes, H. Leighton; Gil, M. Luisa; Yáñez, Alberto (Frontiers in Immunology, 2021)
More mechanistic studies are needed to reveal the hidden details of in vivo-induced trained immunity. Here, using a Candida albicans live vaccine mouse model we show that vaccination protects mice against a secondary infection and increases the number of bone marrow, and especially, splenic trained monocytes. Moreover, vaccination expands and reprograms hematopoietic stem and progenitor cells (HSPCs) early during infection and mobilize them transiently to the spleen to produce trained macrophages. Trained HSPCs are not only primed for myeloid cell production but also reprogramed to produce a greater amount of proinflammatory cytokines in response to a second challenge. Additionally, their adoptive transfer is sufficient to protect mice against reinfection. Mechanistically, autocrine GM-CSF activation of HSPCs is responsible for the trained phenotype and essential for the vaccine-induced protection. Our findings reveal a fundamental role for HSPCs in the trained immune protective response, opening new avenues for disease prevention and treatment.